A ubiquitin carboxyl extension protein secreted from a plant‐parasitic nematode Globodera rostochiensis is cleaved in planta to promote plant parasitism. (28th February 2013) - Chronis, Demosthenis; Chen, Shiyan; Lu, Shunwen; Hewezi, Tarek; Carpenter, Sara C.D.; Loria, Rosemary; Baum, Thomas J.; Wang, Xiaohong
Summary Nematode effector proteins originating from esophageal gland cells play central roles in suppressing plant defenses and in formation of the plant feeding cells that are required for growth and development of cyst nematodes. A gene (GrUBCEP12) encoding a unique ubiquitin carboxyl extension protein (UBCEP) that consists of a signal peptide for secretion, a mono‐ubiquitin domain, and a 12 amino acid carboxyl extension protein (CEP12) domain was cloned from the potato cyst nematode Globodera rostochiensis. This GrUBCEP12 gene was expressed exclusively within the nematode's dorsal esophageal gland cell, and was up‐regulated in the parasitic second‐stage juvenile, correlating with the time when feeding cell formation is initiated. We showed that specific GrUBCEP12 knockdown via RNA interference reduced nematode parasitic success, and that over‐expression of the secreted GrΔSPUBCEP12 protein in potato resulted in increased nematode susceptibility, providing direct evidence that this secreted effector is involved in plant parasitism. Using transient expression assays in Nicotiana benthamiana, we found that GrΔSPUBCEP12 is processed into free ubiquitin and a CEP12 peptide (GrCEP12) in planta, and that GrCEP12 suppresses resistance gene‐mediated cell death. A target search showed that expression of RPN2a, a gene encoding a subunit of the 26S proteasome, was dramatically suppressed in GrΔSPUBCEP12 but not GrCEP12 over‐expression plants when compared with control plants. Together, these results suggest that, when delivered into host plant cells, GrΔSPUBCEP12 becomes two functional units, one acting to suppress plant immunity and the other potentially affecting the host 26S proteasome, to promote feeding cell formation.